Studi Implementasi Program Bakti Sosial Sekolah SDN Jelapat 1 - Nadia Nadia; Arpah Arpah; Hana Azzahra; Ira Syifa Nur Ilham; Theresia Desentalia Sitorus; Risma Rahmadhani; Suhaimi Suhaimi (JURNAL ILMIAH NUSANTARA, 2026)
This study examines the implementation of social activity programs in elementary schools and how they contribute to the development of students' social character. Schools serve not only as places for theoretical learning but also as spaces that support students in understanding social values ​​such as cooperation, empathy, and a sense of responsibility. The method used in this study is a qualitative approach by conducting a literature study, examining various national journal articles related to social activities, character education, and learning programs implemented at the elementary school level. Data collection was carried out through documentation, which was then analyzed using descriptive qualitative methods. The findings of this study indicate that social activities can increase students' awareness, empathy, and responsibility towards the environment and society